Development of a PNGase Rc Column for Online Deglycosylation of Complex Glycoproteins during HDX-MS - Lambert, Thomas; Gramlich, Marius; Stutzke, Luisa; Smith, Luke; Deng, Dingyu; Kaiser, Philipp D; Rothbauer, Ulrich; Benesch, Justin L P; Wagner, Cornelia; Koenig, Maximiliane; Pompach, Petr; Novak, Petr; et al. (Journal of the American Society for Mass Spectrometry, 2023)
Protein glycosylation is one of the most common PTMs and many cell surface receptors, extracellular proteins, and biopharmaceuticals are glycosylated. However, HDX-MS analysis of such important glycoproteins has so far been limited by difficulties in determining the HDX of the protein segments that contain glycans. We have developed a column containing immobilized PNGase Rc (from Rudaea cellulosilytica) that can readily be implemented into a conventional HDX-MS setup to allow improved analysis of glycoproteins. We show that HDX-MS with the PNGase Rc column enables efficient online removal of N-linked glycans and the determination of the HDX of glycosylated regions in several complex glycoproteins. Additionally, we use the PNGase Rc column to perform a comprehensive HDX-MS mapping of the binding epitope of a mAb to c-Met, a complex glycoprotein drug target. Importantly, the column retains high activity in the presence of common quench-buffer additives like TCEP and urea and performed consistent across 114 days of extensive use. Overall, our work shows that HDX-MS with the integrated PNGase Rc column can enable fast and efficient online deglycosylation at harsh quench conditions to provide comprehensive analysis of complex glycoproteins.
Keywords: glykosylace; Polysaccharides; polysacharidy; Glycosylation; Glycoproteins; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; glykopeptidasa; glykoproteiny